Transmission of sheep-bovine spongiform encephalopathy to pigs. (December 2016) - Hedman, Carlos; Bolea, Rosa; Marín, Belén; Cobrière, Fabien; Filali, Hicham; Vazquez, Francisco; Pitarch, José; Vargas, Antonia; Acín, Cristina; Moreno, Bernardino; Pumarola, Martí; Andreoletti, Olivier; et al.
Abstract Experimental transmission of the bovine spongiform encephalopathy (BSE) agent has been successfully reported in pigs inoculated via three simultaneous distinct routes (intracerebral, intraperitoneal and intravenous). Sheep derived BSE (Sh-BSE) is transmitted more efficiently than the original cattle-BSE isolate in a transgenic mouse model expressing porcine prion protein. However, the neuropathology and distribution of Sh-BSE in pigs as natural hosts, and susceptibility to this agent, is unknown. In the present study, seven pigs were intracerebrally inoculated with Sh-BSE prions. One pig was euthanized for analysis in the preclinical disease stage. The remaining six pigs developed neurological signs and histopathology revealed severe spongiform changes accompanied by astrogliosis and microgliosis throughout the central nervous system. Intracellular and neuropil-associated pathological prion protein (PrPSc ) deposition was consistently observed in different brain sections and corroborated by Western blot. PrPSc was detected by immunohistochemistry and enzyme immunoassay in the following tissues in at least one animal: lymphoid tissues, peripheral nerves, gastrointestinal tract, skeletal muscle, adrenal gland and pancreas. PrPSc deposition was revealed by immunohistochemistry alone in the retina, optic nerve and kidney. These results demonstrate the efficient transmission of Sh-BSE in pigs and show for the first time that in this species propagation of bovine PrPSc in a wide range of peripheral tissues is possible. These results provide important insight into the distribution and detection of prions in non-ruminant animals.